Life Among The Piutes : Their Wrongs And Claims - Winnemucca, Sarah, 1844?-1891 (Book collections on Project MUSE., 1994)
This autobiographical work was written by one of the country's most well-known Native American women, Sarah Winnemucca. She was a Paiute princess and a major figure in the history of Nevada; her tribe still resides primarily in the state. Life Among the Piutes deals with Winnemucca's life and the plight of the Paiute Indians. Life Among the Piutes is Winnemucca's powerful legacy to both white and Paiute cultures. Following the oral tradition of Native American people, she reaches out to readers with a deeply personal appeal for understanding. She also records historical events from a unique perspective. She managed to record the Native American viewpoint of whites settling the West, told in a language that was not her own and by a woman during the time when even white women were not allowed to vote. Sarah Winnemucca dedicated her life to improving the living and social conditions for her people. She gave more than 400 speeches across the United States and Europe to gain support for the Paiutes. She died of tuberculosis in 1891. Life Among the Piutes was originally published in 1883